LOCAL INSTRUCTION THEORY ON DIVISION IN MATHEMATICS GASING - Rully Charitas Indra Prahmana; Petra Suwasti (Journal on Mathematics Education, 2014)
Several studies on learning mathematics for rural area's student indicate that students have difficulty in understanding the concept of division operation. Students are more likely to be introduced by the use of the formula without involving the concept itself and learning division separate the concrete situation of learning process. This underlies the researcher to design division operation learning in the Mathematics of GASING (Math GASING), which always starts from concrete to abstract level. The research method used is a design research which describes how the Math GASING make a real contribution of students understanding in the concept of division operation. Keywords: Division Operation, Design Research, Math GASING, Rural Areaâ€™s StudentÂ DOI: http://dx.doi.org/10.22342/jme.5.1.1445.17-26